Synthesis and characterization of nickel oxide nanoparticles by self-propagating low temperature combustion method - Ganachari, Sharanabasava V; Bhat, Ravishankar; Deshpande, Raghunandan; A, Venkataraman (Recent Research in Science and Technology, 2012)
Nickel Oxide (NiO) nanoparticles have been synthesised by self-propagating low temperature Combustion synthesis method using Nickel salt with polyethylene glycol as fuel. As synthesized NiO nanoparticles was characterized by employing Fourier transform infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and Energy dispersive X-ray microanalysis studies (EDAX) techniques and X-ray diffraction (XRD) confirmed the formation of NiO nanoparticles in the range 20 to 40 nm. SEM images clearly shows the NiO particles are in Nano size.